2018
DOI: 10.1017/s0007114518001861
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofBifidobacterium lactisHN019 on inflammatory markers and oxidative stress in subjects with and without the metabolic syndrome

Abstract: Beneficial effects of probiotics have been reported on body weight, lipid and carbohydrate metabolism, inflammatory state and oxidative stress in healthy subjects and in many metabolic and inflammatory diseases. The aim of this study was to evaluate the effects of Bifidobacterium lactis HN019 on inflammatory state and nitro-oxidative stress in patients with and without the metabolic syndrome (MetS). The usual diets of the thirty-three subjects were supplemented with probiotic milk for 90 d. Inflammatory marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 70 publications
0
24
0
1
Order By: Relevance
“…For example, as reported before, Sabico et al have tested multistrain probiotic supplementation in diabetic patients observing after 6 months no effect on leptin level but a significant increase of APN associated with a reduction of inflammation state and an improvement of cardiometabolic profile [44]. Additionally, Bernini et al have demonstrated that Bifidobacterium lactis HN019 supplementation for 90 days improved adiponectin and nitric oxide levels increasing antioxidant defenses in patients [72]. On the other hand, another study has shown that consumption of probiotic soy milk and soy milk does not influence APN level and inflammation state in T2DM patients [73].…”
Section: Adiponectin: Nutritional Interventionsmentioning
confidence: 83%
“…For example, as reported before, Sabico et al have tested multistrain probiotic supplementation in diabetic patients observing after 6 months no effect on leptin level but a significant increase of APN associated with a reduction of inflammation state and an improvement of cardiometabolic profile [44]. Additionally, Bernini et al have demonstrated that Bifidobacterium lactis HN019 supplementation for 90 days improved adiponectin and nitric oxide levels increasing antioxidant defenses in patients [72]. On the other hand, another study has shown that consumption of probiotic soy milk and soy milk does not influence APN level and inflammation state in T2DM patients [73].…”
Section: Adiponectin: Nutritional Interventionsmentioning
confidence: 83%
“…51,52 Several studies have reported that Bifidobacterium imparts beneficial effects on anti-inflammatory, anti-oxidation, anti-obesity, and ZHANG et Al obesity-induced insulin resistance. [53][54][55] Based on the above evidence, we hypothesize that allicin-induced GMT may also have many beneficial effects on energy homeostasis.…”
Section: Zhang Et Almentioning
confidence: 95%
“…Interestingly, this feature was maintained in both CD and UC patients, despite their gut microbiome dysbiosis. Bi dobacterium has been shown to have bene cial effects for human health, such as improving mucosal barrier function and reducing in ammation by producing short-chain fatty acids and vitamins, and is used in probiotics as one treatment option for IBD [34][35][36][37]. A previous Western study analyzing the treatment-naïve CD microbiome showed that Bi dobacterium abundance decreased in CD patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…The high abundance of Bi dobacterium in the gut microbiome of Japanese individuals was considered as a potential factor explaining the low IBD prevalence in Japanese populations; however, in our study, this unique feature was detected not only in healthy individuals but also in IBD patients. Members of the genus Bi dobacterium can have species-dependent effects [34,36,37], and thus further species-level research is needed to understand the role of Bi dobacterium in the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 99%